Intersubjective realities of harm reduction in Costa Rica: Polyphonic voices of homelessness and drug consumption - Caravaca-Morera, Jaime Alonso (Horizonte Sanitario, 2022)
Objective: To understand the experiences of Harm Reduction amongthe voices of homeless people and drug users in Costa Rica.Materials and Methods: A qualitative research with aphenomenological approach that worked with 10 homeless people inCosta Rica during 2019-2020.Results: The materialization of the right to health and the recognitionof the citizenship/humanism of homeless people-drug user were alwayspresent in the lived experiences of the participants. In addition, it wasexplicit that the axes of Humanism, Person-centered Care and therecognition of the Drug Phenomenon as a dimension belonging to thefield of Public Health were neuralgic points of being within the HarmReduction in Costa Rica.Conclusion: One of the major contributions of this study was theunderstanding of the progress of Harm Reduction in a non-place likethe street. The social phenomenological understanding also showedus that the sense of "being" in the world is not something that can bedetermined by primitive and punitive structures. Therefore, any healthcare attempt that delegitimizes the human being at any time or (no)place will be doomed to failure.Keywords: Harm reduction; Homeless; Drugs; Human rights; Publichealth